2021
DOI: 10.3389/fcell.2021.675555
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Ferroptosis-Related lncRNAs Signature Associated With Immune Landscape and Radiotherapy Response in Glioma

Abstract: Recent studies have demonstrated that long non-coding RNAs (lncRNAs) are implicated in the regulation of tumor cell ferroptosis. However, the prognostic value of ferroptosis-related lncRNAs has never been comprehensively explored in glioma. In this study, the transcriptomic data and clinical information of glioma patients were downloaded from TCGA, CGGA and Rembrandt databases. We identified 24 prognostic ferroptosis-related lncRNAs, 15 of which (SNAI3-AS1, GDNF-AS1, WDFY3-AS2, CPB2-AS1, WAC-AS1, SLC25A21-AS1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 51 publications
6
48
0
Order By: Relevance
“…Upregulation of SNHG18 promotes resistance to radiotherapy in glioma by repressing Semaphorin 5A (Zheng et al, 2016). High expressions of PVT1 and SNHG18 in glioblastoma samples as opposed to LGG was validated in the previous study (Zheng et al, 2021). Notably, the role of lncRNAs APCDD1L-AS1, LINC00205, LINC00484, LINC00601, LINC00664, and LINC00886 was first reported and validated in the present study.…”
Section: Discussionsupporting
confidence: 70%
“…Upregulation of SNHG18 promotes resistance to radiotherapy in glioma by repressing Semaphorin 5A (Zheng et al, 2016). High expressions of PVT1 and SNHG18 in glioblastoma samples as opposed to LGG was validated in the previous study (Zheng et al, 2021). Notably, the role of lncRNAs APCDD1L-AS1, LINC00205, LINC00484, LINC00601, LINC00664, and LINC00886 was first reported and validated in the present study.…”
Section: Discussionsupporting
confidence: 70%
“…cell carcinoma, it has not been elucidated in EC. [27][28][29] As presented in the bubble diagram, the prognostic signature was positively correlated with memory CD4 + T cells, M2 macrophages, Tregs, and Tfh cells, whereas cancerassociated fibroblasts (CAFs) and NK cells were negatively correlated with it (Figure 7A, Table S4). Differential analysis of immune cells reported that compared with the low-risk group, plasma cells, endothelial cells, Tfh cells, and Tregs were upregulated in the high-risk group, whereas downregulated immune cells in the high-risk group included CAFs and NK cells (Figure 7B-G).…”
Section: Immune Landscape In Prognostic Signaturementioning
confidence: 93%
“…25,26 Prognostic signatures based on the absolute gene expression level of ferroptosisrelated lncRNAs (falncRNAs) have been recently defined for other solid tumors. [27][28][29] Remarkably, studies on the relationship between EC and falncRNAs are particularly scarce, which still needs to be further elucidated. Accordingly, the identification of falncRNAs to predict the prognosis and immune landscape and immunotherapy response of EC is helpful for the individualized treatment of patients.…”
Section: Introductionmentioning
confidence: 99%
“…These genesignatures constitute a risk-model, predicting the overall survival of the patients. To avoid overfitting, the models were each constructed in one database, e. g. Chinese Glioma Gene Atlas (CGGA), and validated using other databases, e. g. Repository for Molecular Brain in Neoplasia Data (REMBRANDT) or The Cancer Genome Atlas (TCGA) (26)(27)(28)(29)(30)(31)(32). The risk-models are shown and described in Table 1.…”
Section: Ferroptosis-gene Signatures In Gliomamentioning
confidence: 99%